REVIEW : THE EFFECT OF MEDICATION REMINDER APPLICATIONS ON MEDICATION COMPLIANCE IN TYPE 2 DIABETES MELLITUS PATIENTS - Deni Hendra Alamsyah; Yani Mulyani; Marita Kaniawati (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2023)
Diabetes Mellitus (DM) is a medical disorder that is characterized by elevated blood glucose levels. Its prevalence is increasing globally, with Indonesia projected to have 21.3 million type 2 DM patients by 2030. Medication compliance is crucial in managing diabetes, and medication reminder applications can effectively enhance patient adherence. We conducted a systematic review of 10 national and international journals from to 2013-2023 using PubMed, Google Scholar, and Science Direct, focusing on the following keywords: Diabetes, Medication Compliance, Medication Reminder Application. Our findings suggest that patient knowledge and compliance play a pivotal role in the success of therapy management and that medication reminder applications have a positive impact on enhancing medication adherence. Ensuring that patients with diabetes have access to these tools may improve treatment outcomes. Keywords: Diabetes Mellitus Type 2; Medication Compliance; Medication Reminder Application, Medication Adherence; Medication Reminder App